S16 Molecular profiling of the airway microbiome in COPD. (2nd December 2011) - Haldar, K; Lau, K; Bafadhel, M; Brightling, C; Barer, M
Abstract : Introduction: It is hypothesised that bacteria are important in the pathogenesis of COPD exacerbations and clinical expression of disease. To date, most bacteriological research in COPD has been performed using culture based methods. However, novel molecular approaches offer more detailed evaluation of the airway microbiome that may better inform the role of bacteria in COPD. Aims: To characterise the microbial community in COPD and examine whether detectable changes occur with serial longitudinal assessment at stable, exacerbation, follow-up and recovery visits. Methods: 115 COPD patients that were part of a clinical trial had sputum samples collected at the four time points. Patients received antibiotics and / or oral corticosteroids after clinical assessment to treat exacerbations. Follow-up and recovery samples were collected 2 and 6 weeks after the exacerbation sample. Real-time quantitative PCR (qPCR) was performed on sputum DNA using universal 16S gene primers and specific gene targets to quantify total bacterial load and the specific pathogens Haemophilus influenzae, Streptococcus pneumoniae, Moraxella catarrhalis and Staphylococcus aureus . In a subgroup of 30 patients, 454 high-throughput pyrosequencing was performed at each of the 4 visits to examine changes to the global microbiome. Results: Quantitative PCR identified one or more pathogens in 94% of stable samples and 97% of exacerbation samples. There was no significant difference in the total bacterial load or any specific pathogen between longitudinal stable and exacerbation samples. 454 pyrosequencing identified Proteobacteria and Firmicutes to be the dominant groups contributing >80% of the sequence reads at phylum level. Haemophilus, Moraxella and Streptococcus were the dominant groups at genus level. Cluster analysis characterised three groups on the basis of the ratio of Proteobacteria to Firmicutes. No significant differences in patient characteristics were observed between microbiome clusters. There was no significant change across visits in the microbial community at either phylum or genus level. No treatment specific effects on the microbiome were observed. Conclusions: Molecular profiling identifies heterogeneity in the airway microbiome of COPD patients, with dominance of pathogens routinely identified at culture. However, a precise role for bacteria in COPD remains unclear.